2016
DOI: 10.1038/srep37384
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors linked to depression vulnerability are associated with altered cerebellar resting-state synchronization

Abstract: Hosting nearly eighty percent of all human neurons, the cerebellum is functionally connected to large regions of the brain. Accumulating data suggest that some cerebellar resting-state alterations may constitute a key candidate mechanism for depressive psychopathology. While there is some evidence linking cerebellar function and depression, two topics remain largely unexplored. First, the genetic or environmental roots of this putative association have not been elicited. Secondly, while different mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
2
14
0
1
Order By: Relevance
“…Human studies with PTSD patients revealed that cerebellar connectivity is altered in patients compared to control subjects 20 . Environmental factors linked with depression (including post-stroke depression) were also found to be related to cerebellar connectivity 54 . Cerebellar connectivity was implemented in social anxiety and chronic work stress 22 , 55 .…”
Section: Discussionmentioning
confidence: 96%
“…Human studies with PTSD patients revealed that cerebellar connectivity is altered in patients compared to control subjects 20 . Environmental factors linked with depression (including post-stroke depression) were also found to be related to cerebellar connectivity 54 . Cerebellar connectivity was implemented in social anxiety and chronic work stress 22 , 55 .…”
Section: Discussionmentioning
confidence: 96%
“…Proteins in the LRFN family span the plasma membrane, and their extracellular domains are thought to participate in the cell-cell interactions necessary for both neuronal development 69,70 and synapse formation 71 . Lrfn5, along with another member of the Lrfn protein family, Lrfn2, may induce both inhibitory and excitatory presynaptic differentiation in nearby neuronal cells 72 , a process that may play a critical role in brain development and function 73 . As a family, these genes are primarily expressed in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MDD has a complex pattern of altered cerebellar‐cerebral functional connectivity characterized by hypoconnectivity with the PFC and DMN and hyperconnectivity with the visual recognition network and parahippocampal gyrus . Some environmental factors may lead to MDD vulnerability through alterations of the neural oscillatory activity of the cerebellum during resting state . Increased activation in the cerebellum of adolescents with MDD during rewarded sustained attention has been suggested to be a compensatory mechanism for the underactivation of fronto‐striato‐thalamic circuit .…”
Section: Discussionmentioning
confidence: 99%
“…44 Some environmental factors may lead to MDD vulnerability through alterations of the neural oscillatory activity of the cerebellum during resting state. 45 Increased activation in the cerebellum of adolescents with MDD during rewarded sustained attention has been suggested to be a compensatory mechanism for the underactivation of fronto-striato-thalamic circuit. 46 We therefore speculate that increased cerebellar connectivity between the PFC and motor thalamus nuclei in MDD patients may be a compensatory mechanism for the decreased thalamus connectivity and/or an independent abnormality associated with cognitive and emotional dysfunction.…”
Section: Discussionmentioning
confidence: 99%